The Legal Validity of the Civil Servant Appointment Decree as Collateral in a Credit Agreement - Yohana Veronica Carolin; Abdul Salam (JURNAL AKTA, 2024)
All A Decree on the Appointment of Civil Servants is a decree regarding the appointment of Civil Servants issued by a Civil Service Supervisory Officer who has special privileges in the field of civil law. Banks provide credit services to the public whose implementation requires collateral. The approach method that will be used in this research is the normative juridical approach method. This Civil Servant Decree is not part of a securities, because the owner has special privileges which contain legal certainty that the civil servant will receive a fixed salary. Banks as credit providers at this time need to apply appropriate analysis in providing credit to civil servants and the civil servant's decision letter is used as collateral, where later the loan given will be adjusted to the civil servant's salary and the time period determined by the parties. The research results show that the PNS Decree has permanent legal force because it is in the form of a valid decision but cannot be traded, the PNS Decree has economic value in the form of a guarantee of legal certainty that civil servants will receive a definite salary every month. The bank can also ask for liability by default where the bank can ask for compensation, cancellation of the agreement, and fulfillment of achievements plus interest for existing losses. Banks need to apply the principle of prudence in providing credit to their customers. The good faith of customers in paying off their credit if they are no longer civil servants is an important point in this accountability.